Selenoprotein P in Myocardial Infarction With Cardiogenic Shock. Issue 1 (January 2020) - Büttner, Petra; Obradovic, Danilo; Wunderlich, Sebastian; Feistritzer, Hans-Josef; Holzwirth, Erik; Lauten, Philipp; Fuernau, Georg; de Waha-Thiele, Suzanne; Desch, Steffen; Thiele, Holger
ABSTRACT: Background: Reperfusion strategies in acute myocardial infarction (AMI) may result in ischemia reperfusion injury characterized by increased oxidative stress, inflammation, and ultimately death of myocardial tissue which may be of particular importance in infarct-related cardiogenic shock (CS). Many anti-oxidative and immune regulatory processes depend on selenium which in large proportions is bound to circulating selenoprotein P (SelP). Individual SelP patterns may therefore be associated with inflammatory response and possibly mortality in patients with CS post AMI. Methods: In the randomized Intra-Aortic Balloon Pump in cardiogenic Shock II (IABP-SHOCK II)-trial, 600 patients with CS complicating AMI were assigned to therapy with or without IABP. In a predefined biomarker substudy of 147 patients, we analyzed SelP levels 1 and 3 days following randomization. Samples were compared with healthy controls and associations with the unspecific inflammatory marker C-reactive protein (CRP) were analyzed. Results: Compared with controls SelP levels in patients with infarct-related CS were markedly higher (2.7-fold at day 1 and 5.7-fold at day 3 following AMI, all P  < 0.001). Thirty-day mortality was significantly higher in patients with SelP levels above the 75th percentile at day 3 following AMI (26% vs. 46%, P  = 0.045). SelP was significantly proportionally correlated with CRP 1 (R 2  = 0.762, P  < 0.0001) and 3 days (R 2  = 0.777 P  < 0.0001) following AMI. Conclusion: SelP levels are significantly increased post AMI with CS. Higher SelP levels are associated with increased CRP levels indicative for inflammatory processes. Future studies should focus on the characterization of SelP profiles following AMI and the identification of pathomechanisms affected by SelP.